Evaluation of 39 children with stroke regarding etiologic risk factors and treatment - Hergüner, M. Özlem; İncecik, Faruk and Elkay, Mürüvet and Altunbaşak, Şakir and Baytok, Vildan (The Turkish Journal of Pediatrics, 2005)
Stroke etiologies in childhood differ from those in adulthood. While in children, congenital and acquired heart diseases and sickle cell anemia (SCA) are commonly seen causes, atherosclerosis is the main cause in adults. In this study, 39 children admitted to our hospital with ischemic stroke were evaluated according to etiologic factors and treatment regimens with comparison to the literature. Congenital-acquired heart disease and central nervous system infections (meningoencephalitis) were the most common causes in our series. Only one patient had dual pathology. As a result, cardiologic and infectious causes appeared to be the most important etiologic factors, especially in our region. Furthermore, etiologic factors rather than treatment used may play an important role in stroke recurrence.